Methyl 3, 4‐dihydroxybenzoate protects primary cortical neurons against Aβ25–35‐induced neurotoxicity through mitochondria pathway. Issue 9 (3rd July 2013) - Zhou, Xiao‐Wen; Zhang, Zheng; Su, Chao‐Fen; Lv, Ruo‐Hua; Zhou, Xing; Cai, Liang; Wang, Chen‐Yu; Yan, Li; Zhang, Wei; Luo, Huan‐Min
<x xml:space="preserve">Abstract</x> Amyloid‐β peptides (Aβ), which can aggregate into oligomers or fibrils in neurons, play a critical role in the pathogenesis of Alzheimer's disease (AD). Methyl 3, 4‐dihydroxybenzoate (MDHB), a phenolic acid compound, has been reported to have antioxidative and neurotrophic effects. The present study investigated the neuroprotective effects of MDHB against Aβ‐induced apoptosis in rat primary cortical neutons. The primary cortical neurons were pretreated with different concentrations of MDHB for 24 hr, then incubated with 10 μM Aβ25–35 for 24 hr. The results showed that Aβ25–35 could induce neurotoxicity as evidenced by the decreased cell viability and the increased apoptotic rate. In parallel, Aβ25–35 significantly increased the reactive oxygen species accumulation and decreased mitochondrial membrane potential. However, pretreatment of the primary cortical neurons with MDHB could effectively suppress these cellular events caused by Aβ25–35 exposure. In addition, MDHB could increase the level of Bcl‐2, decrease the level of Bax, and inhibit the activation of caspase‐9 and caspase‐3 in Aβ25–35‐treated primary cortical neurons. All these results were beneficial in their protective effect against Aβ‐induced neurotoxicity. Our results suggest that MDHB has a neuroprotective effect that provides a pharmacological basis for its clinical use in the treatment of AD. © 2013 Wiley Periodicals, Inc.